ANALISIS ASUHAN KEPERAWATAN KELUARGA PADA LANSIA DENGAN HIPERTENSI MELALUI INTERVENSI INOVASI AEROBIC LOW IMPACT EXERCISE UNTUK MENURUNKAN TEKANAN DARAH DI RT 003/007 KELURAHAN GROGOL KOTA DEPOK - Niken Dwi Permata Sari, (2023)
Hypertension is a non-communicable disease with no visible symptoms or is called the silent killer. The incidence of hypertension increases every year with one of the causes being a lack of physical activity. Therefore, efforts are needed to treat hypertension with complementary therapy through aerobic low impact exercise, which is an aerobic activity with light movements, moderate intensity, easy to apply and avoid jumping movements. The purpose of this application is to determine the effectiveness of aerobic low impact exercise on reducing blood pressure in the elderly with hypertension. This implementation was carried out for managed clients and resume clients for 6 meetings in 3 weeks. The results of the application found that there was a change in blood pressure in managed clients from 150/100 mmHg to 120/89 mmHg and in resume clients from 167/120 mmHg to 110/90 mmHg, so it can be concluded that aerobic low impact exercise is effective in reducing blood pressure. Community nurses are advised to apply aerobic low impact exercise as a complementary therapy for clients with hypertension.